Graphene‐mesoporous anatase TiO2 nanocomposite: A highly efficient and recyclable heterogeneous catalyst for one‐pot multicomponent synthesis of benzodiazepine derivatives. (27th July 2017) - Shoeb, Mohd; Mobin, Mohammad; Ali, Abad; Zaman, Shamsuz; Naqvi, Alim H.
Abstract : The potential to bias chemical reaction pathways is a significant goal for physicists and material researchers to design revolutionary materials. Recently, two‐dimensional materials have appeared as a promising candidate for exploring novel catalyst activity in organic reaction. In this context, herein we report an easy and efficient synthesis of substituted benzodiazepines in high yields through the graphene‐based mesoporous TiO2 nanocomposite (Gr@TiO2 NCs) catalyst. To validate the merits of the Gr@TiO2 NCs as a catalyst, we have also designed TiO2 nanoparticle (NPs) under similar conditions. Successful comprehension realization of Gr@TiO2 NCs and TiO2 NPs were concluded from the XRD, SEM, HR‐TEM, EDS elemental mapping, FT‐IR, Raman, UV–Vis and TGA analysis. Gr@TiO2 NCs has the propitious catalyst performance (~98%) over the TiO2 NPs (~77%), which could be scrutinized in terms of graphene support toward the TiO2 NPs and enable the large contact area between graphene and TiO2 NPs. Incorporated graphene maintaining TiO2 as a catalytically active and attracting electron to site isolation, as well as protecting TiO2 from oxidative degradation during the reaction. Moreover, the role of graphene is suggested to prolonged reaction duration, yield and unaltered throughout the reaction because of the π‐π interaction between graphene and TiO2 NPs. Additionally, the catalyst is recycled by filtration and reprocessed six times without having a significant loss in its catalytic activity. Abstract : We have successfully synthesized graphene bonded and mesoporous anatase TiO2 NPs through an ex‐situ hybridization strategy. Gr@TiO2 NCs play a role in the reaction mechanism for coupling of o‐phenylenediamine, dimedone, and aldehydes so as to synthesize benzodiazepine derivatives.